Invasion of murine intestinal M cells by Salmonella typhimurium inv mutants severely deficient for invasion of cultured cells. - Clark, M A (1996)
We have examined the role of the Salmonella typhimurium inv locus in invasion of the murine intestine. Previous studies have demonstrated that M cells within the lymphoid-follicle-associated epithelia are the primary site of intestinal invasion by S. typhimurium. In this study, we show that mutants possessing defects in one of two inv genes, invA or invG, which render them severely deficient for invasion of polarized epithelial MDCK cells, retain their ability to actively invade mouse Peyer's patch M cells. The interaction of these mutants with M cells was associated with apical membrane remodelling resembling that induced by wild-type strains. These data demonstrate that Salmonella invasion in vivo can proceed via mechanisms other than those previously defined in cultured cells.